2008
DOI: 10.1038/sj.bjc.6604619
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant hysterectomy for treatment of residual disease in patients with cervical cancer treated with radiation therapy

Abstract: The objective of this retrospective study was to determine the efficacy of adjuvant hysterectomy for treatment of residual disease in cervical carcinoma treated with radiation therapy. Between 1971 and 1996, 1590 patients with carcinoma of the uterine cervix (stages I -IIIb) were treated with radiation therapy. Three months after completion of radiation therapy, the status of local control was investigated, and total abdominal hysterectomy was performed in cases in which central residual disease existed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 35 publications
2
52
0
8
Order By: Relevance
“…There was no difference in terms of survival between the two arms (hysterectomy versus no hysterectomy), but the 5-year local relapse rates were 27% in the external radiation alone arm and 14% in the external radiation therapy followed by extrafascial hysterectomy arm [18]. Other retrospective studies suggested that surgery after external radiation therapy could exert a potential therapeutic impact [3][4][5][6][7][8][9][10], but none of those studies were randomized trials. After 1999, the use of CRT became the new standard for the treatment of cervical cancer Ͼ4 cm [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was no difference in terms of survival between the two arms (hysterectomy versus no hysterectomy), but the 5-year local relapse rates were 27% in the external radiation alone arm and 14% in the external radiation therapy followed by extrafascial hysterectomy arm [18]. Other retrospective studies suggested that surgery after external radiation therapy could exert a potential therapeutic impact [3][4][5][6][7][8][9][10], but none of those studies were randomized trials. After 1999, the use of CRT became the new standard for the treatment of cervical cancer Ͼ4 cm [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…After 1999, the use of CRT became the new standard for the treatment of cervical cancer Ͼ4 cm [1,2]. Several countries (mainly in Europe and Asia) considered CRT as neoadjuvant therapy and proposed hysterectomy in this context [3][4][5][6][7][8][9][10]. Nevertheless, this surgery could impair the postoperative quality of life of patients because there is a potential risk for major morbidities with CRT, which should be clearly balanced with the true therapeutic benefit of such a hysterectomy [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such patients, the role and modalities of completion surgery (after CRT) continue to be debated. In the literature, very few data are available on the results of completion surgery in patients treated with CRT [3][4][5][6][7][8][9][10]. Nevertheless, even if the therapeutic impact of completion hysterectomy continues to fuel debate, the analysis of prognostic factors (and mainly histologic factors) in hysterectomy and lymphadenectomy specimens could add interesting data in order to improve local and distant control for future patients undergoing CRT.…”
Section: Introductionmentioning
confidence: 99%